Cryptococcus gattii Infections in Multiple States Outside the US Pacific Northwest - Harris, Julie R. (Centers for Disease Control and Prevention, 2013)
Clonal VGII subtypes (outbreak strains) of Cryptococcus gattii have caused an outbreak in the US Pacific Northwest since 2004. Outbreak-associated infections occur equally in male and female patients (median age 56 years) and usually cause pulmonary disease in persons with underlying medical conditions. Since 2009, a total of 25 C. gattii infections, 23 (92%) caused by non–outbreak strain C. gattii, have been reported from 8 non–Pacific Northwest states. Sixteen (64%) patients were previously healthy, and 21 (84%) were male; median age was 43 years (range 15–83 years). Ten patients who provided information reported no past-year travel to areas where C. gattii is known to be endemic. Nineteen (76%) patients had central nervous system infections; 6 (24%) died. C. gattii infection in persons without exposure to known disease-endemic areas suggests possible endemicity in the United States outside the outbreak-affected region; these infections appear to differ in clinical and demographic characteristics from outbreak-associated C. gattii. Clinicians outside the outbreak-affected areas should be aware of locally acquired C. gattii infection and its varied signs and symptoms.